2003
DOI: 10.1063/1.1590415
|View full text |Cite
|
Sign up to set email alerts
|

Medium permittivity bismuth zinc niobate thin film capacitors

Abstract: Thin films were fabricated via metalorganic decomposition methods with three compositions: Bi1.5Zn1.0Nb1.5O7, Bi1.5Zn0.5Nb1.5O6.5, and Bi2Zn2/3Nb4/3O7. The Bi1.5Zn0.5Nb1.5O6.5 composition is a low temperature phase with the cubic pyrochlore structure. This phase may undergo a peritectoid decomposition at 700 °C to the high temperature phases of Bi1.5Zn1.0Nb1.5O7 and BiNbO4. Both the Bi1.5Zn1.0Nb1.5O7 and Bi1.5Zn0.5Nb1.5O6.5 cubic pyrochlores show medium room temperature permittivities (150 and 180, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 20 publications
4
75
1
Order By: Relevance
“…For room temperature applications, thin films of ferroelectrics such as (Ba,Sr)TiO 3 (BST) have been extensively studied [1]. Recently, thin films of a nonferroelectric material, Bi 1.5 Zn 1.0 Nb 1.5 O 7 (BZN), which has the cubic pyrochlore structure [2] and a medium permittivity (170 -200), have attracted interest for tunable applications due to their very low losses (~ 5¥10 -4 [3]) and large tunabilities (55 %) [3][4][5][6] at low frequencies (~ 1 MHz). The tunability is defined as e max -e min ( ) e max , where † e min is the minimum measured permittivity at the maximum applied field, and † e max is the dielectric constant at zero bias.…”
Section: Introductionmentioning
confidence: 99%
“…For room temperature applications, thin films of ferroelectrics such as (Ba,Sr)TiO 3 (BST) have been extensively studied [1]. Recently, thin films of a nonferroelectric material, Bi 1.5 Zn 1.0 Nb 1.5 O 7 (BZN), which has the cubic pyrochlore structure [2] and a medium permittivity (170 -200), have attracted interest for tunable applications due to their very low losses (~ 5¥10 -4 [3]) and large tunabilities (55 %) [3][4][5][6] at low frequencies (~ 1 MHz). The tunability is defined as e max -e min ( ) e max , where † e min is the minimum measured permittivity at the maximum applied field, and † e max is the dielectric constant at zero bias.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bi 1.5 Zn 1.0 Nb 1.5 O 7 (BZN) thin films with the cubic pyrochlore structure have attracted interest for integrated capacitor applications because of their relatively high permittivity (~170-220) [1][2][3][4] and dielectric loss tangents (tan ) that were as low as 5 × 10 -4 [1]. Furthermore, BZN thin films exhibit an electric field tunable dielectric constant [1][2][3][4].…”
mentioning
confidence: 99%
“…XRD q-2q scans after the RTA showed that the BZN films crystallized in the cubic pyrochlore structure and were (111) [20]. The short crystallization times likely reflected the relatively low kinetic barrier against crystallization typical for pyrochlore oxides [21].…”
mentioning
confidence: 99%